(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the psychological and sociological aspects of promoting reading among young people. The study employs netnography (internet ethnography) and cognitive research methods to examine young people’s interest in reading books, reading trends in the online environment, and the role of reading in cognitive development. The results help identify factors that encourage reading among youth. Additionally, the role of social networks in shaping reading culture and the socio-psychological formation of reading habits are discussed. The article has practical significance for developing strategies to widely promote reading among young people.